Loss of β-catenin in resident cardiac fibroblasts attenuates fibrosis induced by pressure overload in mice - Xiang, Fu-Li (Nat Commun, 2017)
Cardiac fibrosis is characterized by excessive extracellular matrix deposition that contributes to compromised cardiac function and potentially heart failure. Cardiac pressure overload resulting from trans-aortic constriction in mice leads to cardiac fibrosis and increased Wnt/β-catenin signaling in cardiac fibroblasts. Here, we conditionally induce β-catenin loss of function in resident cardiac fibroblasts using Tcf21 (MerCreMer) or in activated cardiac fibroblasts using periostin (Postn)(MerCreMer). We show that β-catenin loss of function in cardiac fibroblasts after trans-aortic constriction significantly preserves cardiac function, and reduces interstitial fibrosis but does not alter the numbers of activated or differentiated cardiac fibroblasts in vivo. However, β-catenin is specifically required in resident cardiac fibroblasts for fibrotic excessive extracellular matrix gene expression and binds Col3a1 and Postn gene sequences in cultured cardiac fibroblasts after induction of Wnt signaling. Moreover, cardiomyocyte hypertrophy is blunted with cardiac fibroblast-specific loss of β-catenin after trans-aortic constriction in vivo. Thus, Wnt/β-catenin signaling in resident cardiac fibroblasts is required for excessive extracellular matrix gene expression and collagen deposition after trans-aortic constriction.